Evaluación del efecto de la adición de un microencapsulado de extracto de orégano (Origanum vulgare L.) en el retardo de la oxidación lipídica de una salsa tipo mayonesa durante su almacenamiento acelerado. - Caizaluisa Sulca, Josue Alexander (2022)
The objective at this investigation was to evaluate addition effect of a microencapsulated oregano extract in a mayonnaise sauce, for which three samples were prepared: a white base as an indicator with a synthetic antioxidant (EDTA) and two with different concentrations of microencapsulated (a minimum of 0.07% and a maximum of 0.15%); presence fatty acids on this product allowed to determine delay of lipid oxidation with the characterization by the analysis of peroxide index and acidity; for 42 days under an accelerated storage method at two temperatures (45ºC and 55ºC). Resulting in ascending values for three treatments; at 45 ºC the MB indicator sample started with an IP of 1.82 meq O2/kg to 4.53 meq O2/kg, M1 increased from 1.87 to 11.33 meq O2/kg and M2 had a variation at its IP of 1,80 to 4,67 meq O2/kg. Moreover, at 55ºC, average values of 7,33 meq O2/kg were reached for MB, 12,97 meq O2/kg for M1 and 4,80 meq O2/kg for M2. As for the acidity index at 45 ºC the MB treatment went from 0,22 to 0,36 % m/m of acetic acid, M1 culminated with 0,50 % m/m and M2 reached 0,42 % m/m. While in storage at 55 ºC MB was finished with 0,45 % m/m, M1 with 0,50 % m/m and M2 with 0,39 % m/m. Reference was taken to INEN NTE 1640 which indicates a maximum of 10 meq O2/kg for peroxide index. Estimating shelf life of mayonnaise sauce using food degradation kinetics model showed that the best treatment was M2 sample (0.15% microencapsulated) reflecting the antioxidant potential of microencapsulated, estimating a durability of 158 days. Finally, the production costs were made to the best treatment with microencapsulated resulting in a cost of $3.39 on presentation of 250 gr; comparing with treatment costs with EDTA of $3.10 indicates that there is no significant variation.